Adherence to a Dietary Approaches to Stop Hypertension (DASH)-type diet over the life course and associated vascular function: a study based on the MRC 1946 British birth cohort. Issue 5 (6th March 2018) - Maddock, Jane; Ziauddeen, Nida; Ambrosini, Gina L.; Wong, Andrew; Hardy, Rebecca; Ray, Sumantra
Abstract: Little is known about long-term associations between the Dietary Approaches to Stop Hypertension (DASH) diet and conventional cardiovascular (CV)-risk factors as well as novel measures of vascular function. This study aimed to examine whether long-term adherence to a DASH-type diet in a British birth cohort is associated with conventional CV-risk factors and two vascular function markers, carotid intima–media thickness (cIMT) and pulse wave velocity (PWV). Data came from 1409 participants of the Medical Research Council (MRC) National Survey of Health and Development. Dietary intake was assessed at 36, 43, 53 and 60–64 years using 5-d estimated food diaries. The DASH-type diet score was calculated using the Fung index. Conventional CV-risk factors (blood pressure (BP) and lipids), cIMT in the right and/or left common carotid artery and PWV was measured when participants were 60–64 years. Associations between the DASH-type diet score and outcomes were assessed using multiple regression models adjusted for socioeconomic position, BMI, smoking and physical activity. Participants in higher sex-specific quintiles (Q) of the long-term DASH-type diet had lower BP ( P ≤0·08), higher HDL-cholesterol ( P <0·001) and lower TAG ( P <0·001) compared with people in Q1. Participants in Q5 of the long-term DASH-type diet had lower PWV (−0·28sd ; 95 % CI −0·50, −0·07, P trend =0·01) and cIMT (−0·24sd ; 95 % CI −0·44, −0·04, P trend =0·02) compared with participants in the Q1. This association was independent of the conventional CV-risk factors. Greater adherence to a DASH diet over the life course is associated with conventional CV-risk factors and independently associated with cIMT and PWV.